Window dressing in mutual funds - Vikas Agarwal; Gerald D. Gay; Leng Ling (University of Cologne, Centre for Financial Research (CFR), 2014)
We provide a rationale for window dressing where investors respond to conflicting signals of managerial ability inferred from a fund's performance and disclosed portfolio holdings. We contend that window dressers take a risky bet on their performance during a reporting delay period, which affects investors' interpretation of the conflicting signals and hence their capital allocations. Conditional on good (bad) performance, window dressers benefit from higher (lower) investor flows as compared to non-window dressers. Window dressers also have poor past performance, possess little skill, and incur high portfolio turnover and trade costs, characteristics which in turn result in worse future performance.
Keywords: G11; G20; 330; Mutual funds; Window dressing; Portfolio disclosure; Fund flows